SISTEM PENYIRAMAN OTOMATIS BERDASARKAN KELEMBABAN TANAH BERBASIS ARDUINO UNO R3 - Triguntoro, Triguntoro; Kelviandy, Matias Kristian (Neolectura, 2024)
This research designed an automatic irrigation system with an Arduino Uno R3 microcontroller based on soil humidity, which regulates real-time irrigations. In particular, the study focused on the application of a tool for the growth of kangaroo crops with an optimal humidity of 60-85%, using sensor and microcontroller technology to improve crop productivity and quality by avoiding plant stress due to lack or excess of water.